Ketika Purnama Menyentuh Tumbuhan : Kajian Etnobotani dalam Tradisi Padhang Bulan di Candi Jago, Malang - Nur Fadhilla Lailatul Husna; Yukabad Noor Imaniah; Naufal Sulthan Rafi; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to document and preserve local knowledge about the use of plants in the Padhang Bulan tradition at Candi Jago, Tumpang Village, Malang Regency, East Java, including the types, habits, parts used, methods of use, philosophical meanings, and conservation efforts. The research used a qualitative descriptive approach. Data were obtained through interviews, observations, and documentation. Informants were determined using purposive sampling techniques, followed by snowball sampling. The data were analyzed descriptively through the stages of reduction, presentation, and conclusion drawing. The results showed that there were 21 plant species from 13 families, dominated by the Araceae family, with the majority being herbaceous and tree habitus. The most widely used parts of the plants were fresh flowers and leaves, each of which had philosophical meanings in the context of the ritual. Most of the plants are classified as Least Concern and are obtained through cultivation as a form of local conservation. The novelty of this study lies in the integration of ethnobotanical documentation, philosophical meanings, and plant conservation practices into a single framework of ritual analysis, which confirms the role of Padhang Bulan as a medium for the transmission of local knowledge as well as a strategy for preserving plant diversity based on culture.